A universal concept for area‐selective assembly of metal oxide core‐shell nanoparticles, nanorods, and organic molecules via amide coupling reactions. Issue 8 (24th April 2022) - Zubets, Uladzislau; Zhao, Baolin; Park, Hyoungwon; Halik, Marcus
Abstract: The deposition of nanomaterials (NMs) on substrate is a pertinent for a variety of applications in nanometer‐sized electronics, mechanics, or catalysis. This paper establishes a universal and simple approach for assembly of functionalized metal oxide core nanoparticles (NPs) and nanorods (NRs) on a substrate with uniformity, area‐selectivity, and full order control. Particularly, the aluminium oxide (AlOx ) NPs, titanium dioxide (TiO2 ) NRs, and TiO2 NPs functionalized by self‐assembled monolayer (SAM) molecules are deposited on substrate alternatively layer‐by‐layer. This assembling is performed in solution on the pre‐patterned surface with SAM molecules via amide coupling reactions in order to achieve the reaction‐orthogonality. Moreover, this stacking of inorganic NPs/NRs in a terminated implementation is progressed into latter layer of TiO2 NPs functionalized by 1‐aminopyrene molecules representing an example of hybrid organic‐inorganic formation with fluorescence emission. The deposited layers are characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and total internal reflection fluorescence microscope (TIRFM). The significant versatility of stacked metal oxide core‐shell NPs/NRs via based‐solution method represents excellent and efficient applicability in manufacture of hybrid organic–inorganic nanostructure. Abstract : The universal and simple approach for stacking of functionalized metal oxide NPs and NRs by organic self‐assembled monolayer molecules on substrate surface creates an exclusive nanohybrid. This nanostructure consists of assembled NMs on pre‐patterned surface with high area selectivity, uniformity, and full order control by chemical bond. Moreover, the respective formation of organic–inorganic nanohybrid with fluorescence emission molecules is investigated.